Global Trends in Research of Androgen Receptor Associated With Breast Cancer From 2011 to 2020: A Scientometric Analysis - Chen, Lingzhi; Liu, Yiyuan; Cai, Jiehui; Ji, Zeqi; Zou, Juan; Chen, Yaokun; Wu, Jinyao; Zheng, Daitian; Zheng, Jiehua; Chen, Yexi; Li, Zhiyang (Frontiers in Endocrinology, 2022)
Recently, the androgen receptor has been found as a potential prognostic index and therapeutic target for breast cancer. To reveal the current research status and hotspots in this area, we analyzed the characteristics of related publications from 2011 to 2020. All related publications from 2011 to 2020 were retrieved from the Web of Science. Biblioshiny, VOSviewer, and CiteSpace V were applied to obtain the information on annual publications and citations, the highest yielding countries and authors, influential journals and articles, as well as hot keywords. In total, 2,118 documents, including 1,584 original articles and 534 reviews, were retrieved. Annual publication output was rich from 2014 to 2018, reaching the top in 2017. A systematic review written by Lehman et al. in 2011 was the most-cited document and reference. The United States was the leading country with the maximum number of publications, citations, and link strengths with other countries. The journal publishing the most was Oncotarget. Lehmann was the author who had the highest link strengths with other authors. The most highlighted keywords were “androgen receptor” (n = 1,209), “breast cancer” (n = 690), “expression” (n = 545), “breast cancer” (n = 410), “prostate cancer” (n = 290), and so on, revealing the trend from molecular mechanism level to therapeutic use level. The androgen receptor plays a significant role in the development of breast cancers, whereas its therapeutic value seems to be controversial and needs further study. With the help of a scientometric analysis in this field, researchers can clarify the current research status and hotspots worth fully exploring.